Identification of Hippuric Acid and Phenols in the Urine of Workers with Occupational Exposure - Israa J. Hakeem; Melese Abeyie (Adsorption Science & Technology, 2022)
The current study was conducted on workers in the printing industry in Addis Ababa, the capital and largest city of Ethiopia, which has grown significantly in recent years, providing work for a large number of people whose health motivates us to carry out this work. Because these workers handle substances that appear innocuous but are toxic to human health, such as paint products like VOCs, inhaling these volatile and organic solvents is involuntary. If chronic, it manifests in various symptomatic forms in humans, such as changes in psychomotor function or organ damage, highlighting the need to investigate and evaluate their toxicity depending on the degree of aversion and repercussions experienced by those exposed to this type of solvent. The study was conducted on 40 workers who work in randomly selected locations in Addis Ababa, Ethiopia. For the quantification of total hippuric acid and phenols in urine, two different methods were used. Finally, a survey was carried out to obtain information on the level of knowledge of the toxicity of the chemical substances that use the degree of protection; once the results of the quantitative analyses were obtained and supplemented with the data made by the personal interview, it allowed us to obtain the necessary information to carry out the statistical evaluation and thus to interpret the real substance of the occupational exposure of contamination to which these workers are exposed. The total phenols found averaged 226.61±3.62 mg/L, and hippuric acid is 2.126±0.83 g/L. These values indicate benzene and toluene exposure because they exceed WHO reference values in urine.